Methodological Problems in Research of the Economic Science in the Content of Political Economy and Economics (UNWE Yearbook, 2015)
This study is dedicated to some methodological problems and approaches, related to the study of political economy and economics, as well as the accent on clarification of definitions, the subject and the object of the political economy and economics, and the evolution in understanding the modern political economy. The main purposes of this study are: implementation of a greater clarification in methodological aspect in the concept of the both directions of the economic study – political economy and economics, and lighting of the combination of ideas and understandings in the research of the subject of the modern political economy.The developed thesis is that the review and the study of the economic science nowadays should be conducted not backwards to the classic political economy, but forward to the political economy – as a generalizing science of modern political-economic system. Along the long way of development of the political economy, the rich characteristics, the exhibited concepts, the developed ideas, the revealed facts, the found principles and the used instruments are also evidence for that in the modern ideas of the economic science there is a place in partnership for the different competitive directions of the economic science – the political economy and the economics. The modern political economy should be reviewed as a direction of the economic science together with the other direction – what is the economics. The political economy is an independent science within the system of economic sciences. It was historically thus established, so that its subject always related to production and turnover in its integrity. Therefore it was necessary for the science in its base. The market is in the first place for the economics, and its subject, to a great extent, is limited within these frames, dependent on the poor resources and behavior, where the limited, though rational beginning of the economic subject lies. At the same time, the political economy is oriented towards revealing of objective laws related to development of the human society, it historically analyses its development, it explains the economic reality of the contemporary world, it studies the influence of the political process related to undertaking choice decisions. The subject world of the political economy comes to new dimensions. It responds to the theoretical eclecticism, the comparative institutional analysis, the empirics, the importance of economical dynamics and evolution, the formal political analysis, the evolutionary approach to economic research, to the understanding of global political economy, etc. It is that the political-economic approach is objectively called upon and able to develop methodological instrumentation for the research of complex relations, formed in the modern civilization.